Creative class culture - Gerhard, Ulrike (International encyclopedia of geography, 2017)
Creative class culture refers to the circle of understandings, beliefs, and values of a distinctive group of urban dwellers, the so-called creative class, that are expressed by the ethos of a modern urban lifestyle. It is most prevalent in gentrified inner-city neighborhoods that attract people of higher socioeconomic status with specific consumption patterns and high cultural capital. Creative class culture also captures the social and societal impacts of recent urban redevelopment trends in the transforming knowledge society: the global competition among cities for investments, employment, and affluent and well-educated inhabitants. Besides being a very useful concept to include social theory in urban geography, the notion of a creative class culture spurs uneven urban development by favoring a formal institutionalized social class as the most powerful group for urban growth.